READINESS ASSESSMENT ON E-GOVERNMENT IMPLEMENTATION IN THE GOVERNMENT OF MANGGARAI REGENCY OF INDONESIA - Randang D.M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The purpose of this study is to: (1) describe the readiness of Manggarai Regency in the implementation of e-Government; (2) analyze the factors that inhibit the implementation of e-Government in Manggarai Regency; and (3) know the projected implementation of e-Government in Manggarai Regency. Using a descriptive qualitative method witha post-positivism paradigm, this study focused on: (1) analyzing the readiness of e-Government implementation in Manggarai Regency; and (2) the maturity level of e-Government Implementation in Manggarai Regency. The location of the study was in Manggarai Regency, especially in the Information and Communication Agency (leading sector), Development Planning and Research Agency (e-Planning), and Finance Agency (e-Budgeting). Data came from primary and secondary sources. Data were collected through interviews, documentation, and observation. Informants were determined using the purposive sampling technique. The collected data were analyzed using the technique from Miles and Huberman and then validated using a triangulation technique. Findings suggested that the government of Manggarai Regency still has a low level of readiness in the e-Government implementation. Some factors inhibit the implementation of e-Government in Manggarai Regency, including (a) inadequate resources, (b) inadequate infrastructure that supports e-Government, and (c) non-centralized location of regional offices. Besides that, the maturity level of e-Government implementation in Manggarai Regency has reached the e-interaction level because the website of the government of Manggarai Regency already has a “Contact” menu that displays the e-mail address and telephone number. This enables a two-way interaction between the government and the community.